2021
DOI: 10.1016/j.jds.2020.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychological factors on the prognosis of temporomandibular disorders pain

Abstract: Background/purpose The leading symptom of temporomandibular disorders (TMD) is pain, and psychological factors are involved in the persistence of TMD-related pain. Therefore, this study was aimed to analyze the influence of psychological factors on the prognosis of TMD-related pain. Materials and methods The medical records of 486 patients with TMD-related pain were analyzed. Each patient's psychological profile was assessed using the Symptom Checklist-90-Revised (SCL-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Most of the somatization studies used the SCL 90-R test [ 48 ] to measure somatization; since the BSI-18 is a brief validated version of it [ 35 ], the results can be compared. In line with our results, several authors also found that patients with myofascial pain or painful TMD showed a higher degree of somatization [ 41 , 43 , 49 ]. Finally, the OPPERA study [ 19 ] concluded that the somatic symptoms increase the risk of suffering from TMD and are one of the most important psychological predictors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of the somatization studies used the SCL 90-R test [ 48 ] to measure somatization; since the BSI-18 is a brief validated version of it [ 35 ], the results can be compared. In line with our results, several authors also found that patients with myofascial pain or painful TMD showed a higher degree of somatization [ 41 , 43 , 49 ]. Finally, the OPPERA study [ 19 ] concluded that the somatic symptoms increase the risk of suffering from TMD and are one of the most important psychological predictors.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, in the present study, no significant differences were found in anxiety symptoms (BSI-18) in TMD myalgia patients in comparison to controls. In this case, previous experiments using similar measurements, such as SCL-90, also showed varied results [ 7 , 20 , 41 , 42 , 43 ]. This variety of results might be similarly explained by the TMD severity and type, the sample characteristics, and/or possible comorbidities.…”
Section: Discussionmentioning
confidence: 83%
“…Its greater magnitude among professionals in the regions which at the time of data collection experienced a collapse of the health system, and cemeteries with a demand for burials which exceeded the operational capacity of these spaces, can be explained by the daily experience of deaths in alarming numbers. Feelings of impotence, insecurity regarding the provision of adequate personal protective equipment, the lack of a sense of normality and work overload due to the unrestrained advance of the pandemic, are all elements associated with an increase in negative and hostile symptoms [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vagus sinirinin aktivitesi düşük olduğunda kortizol ve sitokin akut stres cevabı yüksek düzeydedir, stresten arınma ise daha yavaştır. 22 Somatizasyon alt ölçeği, baş ağrısı ve çeşitli organ sistemlerinin şikayetleri gibi algılanan fiziksel işlev bozukluklarından kaynaklanan sıkıntıyı yansıtmaktadır ve yaşanan strese cevap olarak gelişebilmektedir. 23 Stresin hastalık ile ilişkilendirildiği mekanizmalardan biri endokrin sistem ile ilgilidir.…”
Section: Stres Hastalık Ilişkisiunclassified